Efektifitas Senam Kaki Terhadap Tingkat Peripheral Arterial Disease Pada Klien DM Tipe 2 di RSAL dr. Midiyato S Tanjungpinang - Widiastuti, Linda; Wati, Liza (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Type 2 Diabetes Mellitus (DM) prevalence grows 40% from 2014-2015 in Tanjung Pinang.Type 2 DM is a metabolism disorders that can cause any chronic complications, such as Peripheral Arterial Disease (PAD) byexamination of the results ankle brachial index (ABI) â‰¤ 0,90 .This research aimed an effectiveness of leg exercises to PAD on type 2 DM client.The research method was quasi experimental quantitative with pre-test and post-test study involves 66 respondents divided into 2 groups: one intervention groups and one control group each of 33 respondents. The Results, the majority of respondents aged 60-74 years (55%), women (80%), suffering from diabetes more than 10 years (50%), a history of hypertension (56%). After four weeks of intervention, the test results significant relationship of age (p=0,000) and suffering from diabetes (p=0,028) on the rate PAD. Significant difference in the rate of PAD before and after the intervention on theone groups: leg exercises(p = 0.000).The ordinal logistic regression test results point out that leg exercises has the strongest effect on the rate PAD (p = 0.033). The conclusion of this research is leg exercises an effectiveness to PAD on type 2 DM client. The recommends research further needs as sociated with other risk factors that affect PAD such as cholesterol levels, serum creatinine and HbA1c. ABI procedures inspection andthe use of leg exercisesas an independent nursing intervention in the nursing treatment of type 2 DM patients.Keywords: Leg Exercises, Peripheral Arterial Disease, Type 2 Diabetes